The positive evidence bias in perceptual confidence is unlikely post-decisional. Issue 1 (26th July 2022) - Samaha, Jason; Denison, Rachel
Abstract: Confidence in a perceptual decision is a subjective estimate of the accuracy of one's choice. As such, confidence is thought to be an important computation for a variety of cognitive and perceptual processes, and it features heavily in theorizing about conscious access to perceptual states. Recent experiments have revealed a "positive evidence bias" (PEB) in the computations underlying confidence reports. A PEB occurs when confidence, unlike objective choice, overweights the evidence for the correct (or chosen) option, relative to evidence against the correct (or chosen) option. Accordingly, in a perceptual task, appropriate stimulus conditions can be arranged that produce selective changes in confidence reports but no changes in accuracy. Although the PEB is generally assumed to reflect the observer's perceptual and/or decision processes, post-decisional accounts have not been ruled out. We therefore asked whether the PEB persisted under novel conditions that addressed two possible post-decisional accounts: (i) post-decision evidence accumulation that contributes to a confidence report solicited after the perceptual choice and (ii) a memory bias that emerges in the delay between the stimulus offset and the confidence report. We found that even when the stimulus remained on the screen until observers responded, and when observers reported their choice and confidence simultaneously, the PEB still emerged. Signal detection-based modeling showed that the PEB was not associated with changes to metacognitive efficiency, but rather to confidence criteria. The data show that memory biases cannot explain the PEB and provide evidence against a post-decision evidence accumulation account, bolstering the idea that the PEB is perceptual or decisional in nature.